Confucian Ethics, Christian Ethics and the Principlist Approach in Biomedical Ethics - Lowe, Gee Y (Journal of Research for Christianity in China (JRCC), 2025)
With the rapid advance in technology, the world is confronted with a new set of ethical challenges.   China, in the height of her modernization project, certainly would feel the crunch of such onslaught.   This paper examines Confucian ethics in light of a major, bioethical approach of the West.